THE 21ST CENTURY LEADERSHIP CHARACTERISTICS OF ADMINISTRATORS FOR BALLET MAJOR IN SHENYANG CONSERVATORY OF MUSIC UNDER LIAONING PROVINCE IN PEOPLE'S REPUBLIC OF CHINA - Wenhao, Lu; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (วารสารวิจัยธรรมศึกษา, 2023)
The objectives of this research were: (1) to propose the 21st century leadership characteristics of administrators for Ballet Major at Shenyang Conservatory of Music under Liaoning Province in the People's Republic of China.; and (2) to develop the future wheel of the 21st century leadership characteristics of administrators for Ballet Major at Shenyang Conservatory of Music under Liaoning Province in the People's Republic of China. The Delphi technique was used in this research. The key informant was an 18-member expert group composed mainly of ballet management personnel from Shenyang Conservatory of Music in Shenyang, Liaoning Province. Through two rounds of the Delphi technique, data were collected through open-ended interviews and a 5-point rating scale questionnaire. Median, mode and Inter Quartile Range were used for data analysis and content analysis was employed. The research findings revealed that; (1) the 21st century leadership characteristics of administrators for Ballet Major at Shenyang Conservatory of Music consisted of six dimensions: thinking, quality, team building, self-renewal, innovation and future practice; and (2) the researcher developped an image of the future wheel from the result of research objective 1.